PENINGKATAN PROFITABILITAS BANK SWASTA NASIONAL MELALUI BAD KREDIT SEBAGAI MEDIASI - Devi anggraeni; Ana Kadarningsih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to see the effect of Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Company Size (Size) on Return On Assets (ROA) through Non Performing Loans (NPL). The object of this research is 180 secondary data from the financial statements of the Financial Services Authority, but there are only 164 data because the normality of the data does not reach 0.05. The method of data analysis in this research is descriptive analysis, data normality test, path analysis test and sobel test. The tool or application used to analyze the data in this study is SPSS v.24 software. The results of this study indicate that the LDR variable has a significant effect on ROA, the CAR variable has a significant effect on ROA, the Size variable has a significant effect on ROA, the NPL variable has no significant effect on ROA, the LDR, CAR and Size variables on ROA through NPL cannot mediate.